2020
DOI: 10.52922/sb04527
|View full text |Cite
|
Sign up to set email alerts
|

Changes in online gambling during the COVID-19 pandemic

Abstract: This study explores the potential for increased online gambling as a result of COVID-19 social distancing measures. Questions were included in an omnibus survey employing an online panel sample, with data collected in early April 2020. The results showed that almost a quarter of respondents had participated in online gambling in the previous month. Ten percent had increased their participation in at least one form of online gambling, while 14 percent had decreased their involvement. Those betting on sporting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…A greater number of studies estimated the increase in online gambling specifically [24,28,31 ▪ ,35,36 ▪ ,37,39,41]. The lowest estimate was provided by one of the few longitudinal studies, the YouGov weighted panel in Great Britain [31 ▪ ] that showed an increase in online gambling from 1.5% in October 2019 to 2.3% in May 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A greater number of studies estimated the increase in online gambling specifically [24,28,31 ▪ ,35,36 ▪ ,37,39,41]. The lowest estimate was provided by one of the few longitudinal studies, the YouGov weighted panel in Great Britain [31 ▪ ] that showed an increase in online gambling from 1.5% in October 2019 to 2.3% in May 2020.…”
Section: Resultsmentioning
confidence: 99%
“…A single study found that moderate risk but not problem gambling status was associated with increased gambling [30]. Younger age was a significant correlate in five studies [24,26,28,35,39], one of which also found that older age was also a correlate [26]. Men were found to be at increased risk in three studies [26,31 ▪ ,35], and women in another [29 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other online gambling activities, such as slots, casino games, and poker, are illegal in Australia and remained available only on offshore gambling sites. Early in the shutdown, various Australian sources reported increases in online gambling expenditure ranging from 20% to 142% 2 . What these figures specifically represent remains unclear as details regarding their calculation and operationalization are not publicly available in all cases.…”
mentioning
confidence: 99%
“…Penerapan protokol kesehatan yang konsisten memerlukan kebijakan yang mendukung, sarana dan prasana yang memadai serta edukasi dan komunikasi perubahan perilaku yang dapat menjangkau seluruh lapisan masyarakat dengan informasi yang mudah dipahami, akurat, menarik, dan dapat mendorong terjadinya adopsi perilaku pencegahan. (Brown, 2020;Meutia, 2020) Penerapan IPTEK edukasi kesehatan berbasis media pada remaja merupakan sarana pendidikan bagi remaja untuk belajar dengan memanfaatkan alat bantu media pembelajaran yakni kegiatan penyuluhan menggunakan media booklet dan video pembelajaran dengan melibatkan guru untuk ikut berpastisipasi dalam edukasi kesehatan sebagai upaya pencegahan COVID-19. (Meutia, 2020) Oleh karena itu, pelaksana selaku Dosen STIK Budi Kemuliaan melakukan inisiasi upaya preventif dengan edukasi kesehatan sebagai upaya pencegahan penularan COVID-19 di SMA N 57 Jakarta Barat.…”
Section: Pendahuluanunclassified